The Role of miR-181c in Mechanisms of Diabetes-Impaired Angiogenesis: An Emerging Therapeutic Target for Diabetic Vascular Complications - Solly, Emma L.; Psaltis, Peter J.; Bursill, Christina A.; Tan, Joanne T. M. (Frontiers in Pharmacology, 2021)
Diabetes mellitus is estimated to affect up to 700 million people by the year 2045, contributing to an immense health and economic burden. People living with diabetes have a higher risk of developing numerous debilitating vascular complications, leading to an increased need for medical care, a reduced quality of life and increased risk of early death. Current treatments are not satisfactory for many patients who suffer from impaired angiogenesis in response to ischaemia, increasing their risk of ischaemic cardiovascular conditions. These vascular pathologies are characterised by endothelial dysfunction and abnormal angiogenesis, amongst a host of impaired signaling pathways. Therapeutic stimulation of angiogenesis holds promise for the treatment of diabetic vascular complications that stem from impaired ischaemic responses. However, despite significant effort and research, there are no established therapies that directly stimulate angiogenesis to improve ischaemic complications such as ischaemic heart disease and peripheral artery disease, highlighting the immense unmet need. However, despite significant effort and research, there are no established therapies that directly stimulate angiogenesis in a clinical setting, highlighting the immense unmet need. MicroRNAs (miRNAs) are emerging as powerful targets for multifaceted diseases including diabetes and cardiovascular disease. This review highlights the potential role of microRNAs as therapeutic targets for rescuing diabetes-impaired angiogenesis, with a specific focus on miR-181c, which we have previously identified as an important angiogenic regulator. Here we summarise the pathways currently known to be regulated by miR-181c, which include the classical angiogenesis pathways that are dysregulated in diabetes, mitochondrial function and axonal guidance, and describe how these relate both directly and indirectly to angiogenesis. The pleiotropic actions of miR-181c across multiple key angiogenic signaling pathways and critical cellular processes highlight its therapeutic potential as a novel target for treating diabetic vascular complications.